Combinations of laxatives and green banana biomass on the treatment of functional constipation in children and adolescents: a randomized study - Vanessa Mello Granado Cassettari; Nilton Carlos Machado; Pedro Luiz Toledo de Arruda Lourenção; Marry Assis Carvalho; Erika Veruska Paiva Ortolan (Elsevier, 2019)
Objectives: Evaluate the effect of combinations of green banana biomass and laxatives in children and adolescents with chronic constipation. Methods: This was a randomized study of 80 children and adolescents with functional constipation according to the Rome IV Criteria, who were divided into five groups: (1) green banana biomass alone; (2) green banana biomass plus PEG 3350 with electrolytes; (3) green banana biomass plus sodium picosulfate; (4) PEG 3350 with electrolytes alone; and (5) sodium picosulfate alone. Primary outcome measure was the reduction of the proportion of patients with Bristol Stool Form Scale ratings 1 or 2. Secondary outcome measures were: increase of the proportion of >3 bowel movements/week and reduction of the proportion of fecal incontinence, straining on defecation, painful defecation, blood in stool, abdominal pain, and decreased laxative doses. Results: On consumption of green banana biomass alone, a statistically significant reduction was observed in the proportion of children with Bristol Stool Form Scale rating 1 or 2, straining on defecation, painful defecation, and abdominal pain. Conversely, no reduction was observed in fecal incontinence episodes/week, blood in stool, and no increase was observed in the proportion of children with >3 bowel movements/week. The percentage of children who required decreased laxative dose was high when green banana biomass was associated with sodium picosulfate (87%), and PEG 3350 with electrolytes (63%). Green banana biomass alone and associated with laxatives was well tolerated, and no adverse effects were reported. Conclusion: Green banana biomass is advantageous as an adjunct therapy on functional constipation, mainly for reducing doses of laxatives. Resumo: Objetivos: Avaliar o efeito das combinações da biomassa de banana verde e laxantes em crianças e adolescentes com constipação crônica. Métodos: Estudo randomizado de 80 crianças e adolescentes com constipação funcional de acordo com os Critérios de Roma IV divididos em cinco grupos: 1) Somente biomassa de banana verde; 2) Biomassa de banana verde mais PEG 3350 com eletrólitos; 3) Biomassa de banana verde mais picossulfato de sódio; 4) PEG 3350 somente com eletrólitos e 5) somente picossulfato de sódio. O desfecho primário foi a redução da proporção de pacientes com as classificações 1 ou 2 da Escala de Bristol para Consistência de Fezes. Os desfechos secundários foram: aumento da produção de > 3 evacuações/semana e redução da proporção de incontinência fecal, esforço na defecação, defecação dolorosa, sangue nas fezes, dor abdominal e redução nas dose de laxantes. Resultados: No consumo somente de biomassa de banana verde há uma redução estatisticamente significativa na proporção de crianças com classificação 1 ou 2 da Escala de Bristol para Consistência de Fezes, esforço na defecação, defecação dolorosa e dor abdominal. Por outro lado, não houve redução nos episódios fecais/semana de incontinência, sangue nas fezes e nenhum aumento na proporção de crianças com > 3 evacuações/semana. O percentual de crianças que tiveram sua dose de laxante reduzida foi alto quando a biomassa de banana verde foi associada a picossulfato de sódio (87%) e PEG 3350 com eletrólitos (63%). A biomassa de banana verde sozinha e associada a laxantes foi bem tolerada e não houve efeitos adversos relatados. Conclusão: A biomassa de banana verde é vantajosa como uma terapia adjuvante na constipação funcional, principalmente na redução das doses de laxantes. Keywords: Constipation, Dietary fiber, Green banana, Green banana biomass, Resistant starch, Palavras-chave: Constipação, Fibra dietética, Banana verde, Biomassa de banana verde, Amido resistente